Pendidikan Demokrasi, Persaudaraan, dan Persatuan Indonesia dalam terang Dokumen Persaudaraan Manusia (2019) - Jawa, Konstantinus Frederikus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2019)
Education is a medium to bring people towards enlightenment. Education is meant to foster students or young people to be able to embrace life with maturity in faith, personal resilience, and sensitivity to social situations, especially changes that happen today. The spirit of national democracy in Indonesia can be realised through values education in schools so that these become material for a character building process. Values internalised in the education comprise of respect, care, acceptance, solidarity, appreciation, and sensitivity to the suffering of others. In being compassionate to the suffering others, students are called to come out of their comfort zones and to get involved with people who suffer and are in need, especially those who are victims of injustice due to the system in the society. The cultivation of human compassion can be carried on by promoting fraternity, that is, through the real encounters with people of different backgrounds, religions, races, and ethnicities. Building human fraternity in education asks that students are fostered to exercise dialogue of life and are given opportunities to encounter others in living communication. Through the real encounters, they may sense the actual changes in the social reality so that education is not limited to scientific achievements, but touches their affective and psychomotor aspects as well.